1985
DOI: 10.1128/jb.161.1.393-401.1985
|View full text |Cite
|
Sign up to set email alerts
|

Glycine betaine transport in Escherichia coli: osmotic modulation

Abstract: Exogenous glycine betaine highly stimulates the growth rate of various members of the Enterobacteriaceae, including Escherichia coli, in media with high salt concentrations (D. Le Rudulier and L. Bouillard, Appi. Environ. Microbiol. 46:152-159, 1983). In a nitrogen-and carbon-free medium, glycine betaine did not support the growth of E. coli either on low-salt or high-salt media. This molecule was taken up by the cells but was not catabolized. High levels of glycine betaine transport occurred when the cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(110 citation statements)
references
References 34 publications
(30 reference statements)
6
103
0
Order By: Relevance
“…These values correspond to a concentration gradient of 1:45 and 1 : 770 for the cells grown in low-or high-salt medium, respectively [20]. This is in agreement with studies done with other bacteria such as Klebsiella penumoniae [16] and Escherichia coli [21].…”
Section: Variations In the Response Of Salt-stressed Rhizobium Strainsupporting
confidence: 90%
“…These values correspond to a concentration gradient of 1:45 and 1 : 770 for the cells grown in low-or high-salt medium, respectively [20]. This is in agreement with studies done with other bacteria such as Klebsiella penumoniae [16] and Escherichia coli [21].…”
Section: Variations In the Response Of Salt-stressed Rhizobium Strainsupporting
confidence: 90%
“…Since hydroxyectoine apparently functions well as an extracellular (and/or periplasmic) bioprotector during drying, it was of interest to determine whether it can also protect the intracellular environment. Hydroxyectoine is accumulated by E. coli under high osmolarity conditions, but is not used as a carbon source [11,12], and therefore behaves like glycine betaine [15,16]. It should be possible, therefore, to load E. coli with hydroxyectoine simply by incorporating it into high osmolarity growth medium, after which desiccation tolerance can be assessed; the success of this loading strategy can be monitored by its effect on trehalose biosynthesis, which is expected to be reduced, as described for media supplemented with glycine betaine [17].…”
Section: Inclusion Of Hydroxyectoine In High Osmolarity Growth Mediummentioning
confidence: 99%
“…Synthetic betaines help define the characteristics required for accumulation. Perroud and Le Rudulier [15] concluded that the carboxyl group is essential and that its close proximity to the quaternary nitrogen increases the inhibition of radiolabeled-glycine betaine uptake by analogues. Accumulation was not demonstrated; such work does not distinguish competitive accumulation from inhibition of an uptake port.…”
Section: Betainementioning
confidence: 99%